A Cristo moreno in Barcelona: The Staging of Identity-Based Unity and Difference in the Procession of the Lord of Miracles - Fernandez-Mostaza, M. Esther (Religions, 2018)
The procession known as Lord of Miracles is a massive religious phenomenon that takes place in various cities around the world in October. The purpose of this study is to describe and analyze certain elements of the procession, which champion not only the idea of unity (religious, cultural, ethnical, and national), but also the sociocultural differences. With this in mind, we conducted ethnographical research focused on the processions that took place in Barcelona, Spain, in 2016 and 2017. Along with a number of practices and talks intended to activate and strengthen the image of religious unity (Brothers in Christ) and national unity (Brothers of Peru), there are certain dynamics that point to differences, which call that unity into question. Specifically, we focused our study on two seasons of the procession: the scissors dance and the Marian, both dances for the Lord. However, the type of interaction that happens with each of them shows inner differences, which the members establish with the image of the Cristo moreno. These differences are expressed in the special-temporal location of certain stationswhich represent subordinate sociocultural manifestationsand in the type of interaction, which the members establish with the image of the Cristo moreno.